REVIEW ARTICLENeurodegeneration with brain iron accumulation - Gregory, Allison; Hayflick, Susan J. (Folia Neuropathologica, 2005)
Neurodegeneration with brain iron accumulation (NBIA) describes a group of progressive extrapyramidal disorders with radiographic evidence of focal iron accumulation in the brain, usually in the basal ganglia. Patients previously diagnosed with Hallervorden-Spatz syndrome fall into this category. Mutations in the PANK2 gene account for the majority of NBIA cases and cause an autosomal recessive inborn error of coenzyme A metabolism called pantothenate kinase-associated neurodegeneration (PKAN). PKAN is characterized by dystonia and pigmentary retinopathy in children or speech and neuropsychiatric disorders in adults. In addition, a specific pattern on brain MRI, called the eye-of-the-tiger sign, is virtually pathognomonic for the disease. Pantothenate kinase is essential to coenzyme A biosynthesis, and the PANK2 protein is targeted to the mitochondria. Hypotheses of PKAN pathogenesis are based on the predictions of tissue-specific coenzyme A deficiency and the accumulation of cysteine-containing substrates. Identification of the major NBIA gene has led to more accurate clinical delineation of the diseases that comprise this group, a molecular diagnostic test for PKAN, and hypotheses for treatment.